Dog saliva – an important source of dog allergens. Issue 5 (7th March 2013) - Polovic, N.; Wadén, K.; Binnmyr, J.; Hamsten, C.; Grönneberg, R.; Palmberg, C.; Milcic‐Matic, N.; Bergman, T.; Grönlund, H.; van, M.
Abstract Background Allergy to dog (Canis familiaris) is a worldwide common cause of asthma and allergic rhinitis. However, dander extract in routine diagnostics is not an optimal predictor of IgE‐mediated dog allergy. Our objective was to evaluate saliva as an allergen source for improved diagnostics of allergy to dog. Methods IgE‐binding proteins in dog saliva and dander extract were analysed by immunoblot and mass spectrometry (LC‐MS/MS) using pooled or individual sera from dog‐allergic patients (n = 13). Sera from 59 patients IgE positive to dander and 55 patients IgE negative to dander but with symptoms to dog were analysed for IgE against saliva and dander by ELISA. Basophil stimulation with dog saliva and dander extract was measured by flow cytometry among three dog‐allergic patients. Additionally, IgE‐binding protein profiles of saliva from different breeds were investigated by immunoblot. Results Greater number and diversity of IgE‐binding proteins was found in saliva compared to dander extract and varied among dog breeds. In saliva, Can f 1, 2, 3 and 6 were identified but also four new saliva allergen candidates. The majority of the 59 dog dander–positive sera (n = 44) were IgE positive to dog saliva. Among patients IgE negative to dander, but with symptoms to dog, 20% were IgE positive to saliva. The biological activity of saliva was confirmed by basophil degranulation. Conclusions Dog saliva is an allergen source for improved diagnostics of dog allergy. The IgE‐binding protein profile of saliva from different dogs varies.